Long-term mortality after poisoning with antipsychotics. (21st April 2017) - Toft, Stine; Horwitz, Henrik; Dalhoff, Kim Peder
Abstract: Introduction: The objective of this study was to investigate the long-term mortality and cause of death after deliberate self-poisoning with antipsychotics. Furthermore, we investigated the risk of repeated self-poisoning after a first episode of poisoning with antipsychotics. Methods: We identified patients with antipsychotic poisoning from the Danish Poison Information Centre Database and correlated their personal identification number with four Danish national registries related to health aspects. Results: From August 2006 to December 2013 we identified 2289 patients poisoned with antipsychotic agents. The average age of the patients was 35.6 years (SD 14.3) and 68.5% were women. Eleven patients died during the first 30 days, and at the end of follow-up in March 2014, 150 patients were deceased, leading to a mortality rate of 2.1 per 100 person-years and a standardized mortality ratio of 9.0. The most common causes of death were poisoning (29%) and violent suicide (18%) – however half of the patients died from natural reasons. 643 patients (28%) repeated the poisoning once or more. Conclusions: Poisoning with antipsychotics was associated with an increased risk of death. Most of these deaths were preventable, and this highlights the need for secondary prophylaxis following a suicide attempt.